2021
DOI: 10.3390/brainsci11030313
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Two MMPI-2-Based Models of Personality in Predicting Driving Behavior. Can Demographic Variables Be Disregarded?

Abstract: The driver’s personality is a key human factor for the assessment of the fitness to drive (FTD), affecting driving decisions and behavior, with consequences on driving safety. No previous study has investigated the effectiveness of Minnesota Multiphasic Personality Inventory (MMPI)-2 scales for predicting the FTD. The present study aimed to compare two MMPI-2-based models of normal and pathological personality traits (i.e., Inventory of Driving-related Personality Traits (IVPE)-MMPI vs. Personality Psychopatho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 135 publications
1
8
0
Order By: Relevance
“…Finally, age significantly and negatively affected all the driving subtasks. In agreement with previous studies [35,49,50], this result suggests that with the increase of age, the male driver's driving abilities decrease due to age-related decline in cognitive and psychomotor functioning [58][59][60][61][62], with consequences for driving capabilities. The negative correlation between age and cognition observed in this study supported this conclusion.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Finally, age significantly and negatively affected all the driving subtasks. In agreement with previous studies [35,49,50], this result suggests that with the increase of age, the male driver's driving abilities decrease due to age-related decline in cognitive and psychomotor functioning [58][59][60][61][62], with consequences for driving capabilities. The negative correlation between age and cognition observed in this study supported this conclusion.…”
Section: Discussionsupporting
confidence: 92%
“…Models were tested, controlling for participants' age as a covariate, in a sample of active male drivers. Considering our previous findings [29] and those presented in the study of Ruginski et al [30]: (a) the mediated mediation of both the transformation skills was expected to significantly predict measures of both resilience of attention and perceptual speed, (b) mental rotation only is expected to significantly mediate the relationship between cognition and reaction speed, (c) the negative effect of age was expected on each prerequisite for fitness-to-drive [29,[35][36][37], and (d) the positive effects of overall cognitive functioning were expected to be present on resilience of attention and perceptual speed but not on reaction and motor speed [29].…”
Section: Introductionmentioning
confidence: 68%
“…Early studies on personality showed that impulsivity [ 36 ], aggressiveness, sensation-seeking, antisocial behavior, extraversion, and hostility characterize drinker drivers. Among these, sensation-seeking was shown as the personality trait with the most consistent predictive validity on driving measures [ 37 , 38 , 39 , 40 ]. Higher sensation seekers were more likely to drive after drinking alcohol, without wearing safety belts, and show low-risk aversion [ 41 , 42 , 43 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, few studies investigated the role of pathological personality traits in the evaluation of psychological fitness to drive [ 40 , 46 , 47 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation